The IDEAL study: MRI for suspected deep endometriosis assessment prior to laparoscopy is equally reliable as radiological imaging as a complement to transvaginal ultrasonography - Bielen,D; Tomassetti,C; Van,Schoubroeck D; Vanbeckevoort,D; De,Wever L; Vanden,Bosch T; D'Hooghe,T; Bourne,T; D'hoore,A; Wolthuis,A; Van,Cleynenbreughel B; Meuleman,C; et al. (Ultrasound in Obstetrics and Gynecology, 2020)
OBJECTIVES: this prospective observational study compared the value of magnetic resonance imaging (MRI) complementary to transvaginal ultrasonography (TV-US) to our standard preoperative assessment of patients with endometriosis referred for surgery in a tertiary care academic center. Based on the extent to which endometriosis affects reproductive organs, bowel, ureters, bladder or other abdominal organs, the surgery will be carried out by gynecologists only or by a multidisciplinary team involving abdominal surgeons and/or urologists. METHODS: In 74 women with clinically suspected deep endometriosis (DE) the standard preoperative imaging, i.e. an expert transvaginal ultrasonography (TV-US), complemented by an intravenous urography (IVU) for the evaluation of the ureters, and a double contrast barium enema (DCBE) for the evaluation of the rectum, sigmoid and caecum was compared with an expert TV-US complemented by a 'one-stop' abdominal and pelvic magnetic resonance imaging (MRI). The findings of the laparoscopy were the reference standard to provide an answer to the question if a 'one-stop' abdominal/pelvic MRI is equally reliable as our standard radiological imaging as a complement to transvaginal ultrasonography for preoperative triaging of patients with suspected urological and intestinal involvement by DE in tertiary care centers. RESULTS: The standard preoperative imaging as well as the combined findings of the TV-US and the MRI allowed a correct stratification for a monodisciplinary approach by gynecologists or a multidisciplinary approach in 90.5% of the patients. Both TV-US and DCBE underestimated the severity of the rectal involvement in 2.7%, whereas TV-US and/or DCBE overestimated it in 6.8% of the patients. CONCLUSIONS: In conclusion, complementary to an expert transvaginal ultrasound (TV-US) a 'one-stop' magnetic resonance imaging (MRI) predicts the intra-operative findings equally well as the standard radiological imaging (IVU and DCBE) in patients re